2001
DOI: 10.1016/s0735-1097(00)01155-4
|View full text |Cite
|
Sign up to set email alerts
|

Lack of efficacy of atenolol for the prevention of neurally mediated syncope in a highly symptomatic population: a prospective, double-blind, randomized and placebo-controlled study

Abstract: The recurrence of neurocardiogenic syncope in highly symptomatic patients treated with atenolol is similar to that of patients treated with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(42 citation statements)
references
References 31 publications
2
36
0
4
Order By: Relevance
“…91 Atenolol was no more effective than placebo in preventing recurrent syncope in another double-blind randomized clinical trial. 121 However, in a meta analysis of a prespecified, prestratified substudy of POST 1 and a large earlier observational study, there was evidence of benefit in patients older than 40 years. 122 A prospective, multicenter, randomized clinical trial is now testing this effect (POST 5).…”
Section: Section 3: Vasovagal Syncope Definitionmentioning
confidence: 97%
“…91 Atenolol was no more effective than placebo in preventing recurrent syncope in another double-blind randomized clinical trial. 121 However, in a meta analysis of a prespecified, prestratified substudy of POST 1 and a large earlier observational study, there was evidence of benefit in patients older than 40 years. 122 A prospective, multicenter, randomized clinical trial is now testing this effect (POST 5).…”
Section: Section 3: Vasovagal Syncope Definitionmentioning
confidence: 97%
“…b-adrenergic blocking drugs have failed to be effective in five of six long-term follow-up controlled studies. [14][15][16][17][18][19] Vasoconstrictor drugs are potentially more effective in orthostatic hypotension caused by autonomic dysfunction than in neurally-mediated syncope. Etilefrine proved to be ineffective.…”
Section: Causes Of Loss Of Consciousnessmentioning
confidence: 99%
“…Other studies, however, have reported significantly larger recurrence rates between 24 and 61% [9, 10, 11]. In addition, drug therapy, although the most common form of therapy for these patients, has not been shown to be effective in most placebo-controlled studies [5, 12, 13, 14]. Accordingly, following the publication of several early positive pilot studies using pacemaker therapy [15, 16, 17], four larger positive studies [1, 11, 18, 19, 20]that all demonstrated considerable efficacy of pacing therapy in this disorder led to the inclusion of NCS in the pacemaker indication guidelines as a IIA indication (level of evidence B) for pacemaker therapy.…”
Section: Discussionmentioning
confidence: 99%